Intermediate Input Linkage and Carbon Leakage - Zengkai Zhang; ZhongXiang Zhang (Fondazione Eni Enrico Mattei (FEEM), 2016)
Climate regulations tend to target energy intensive sectors whose products are widely used in industrial production as intermediate inputs, such as electricity, and the carbon abatement may be partially offset by intermediate input-led leakage. This paper aims to examine the impact of intermediate input linkage on the carbon leakage both theoretically and empirically. On the theoretical part, we develop a Harberger-type model with an input-output linkage structure, identify four leakage effects and derive closed-form solutions for these leakage effects. On the empirical part, we build a computable general equilibrium model of China for empirical simulation and introduce Structural Decomposition Analysis to link both the theoretical and empirical models. By imposing a carbon price on the electricity generation sector, our results show significant carbon leakage. Our decomposition analysis further suggests that such a leakage is mainly through the production substitution effect, followed by the multiplier effect. Both of the two effects are closely related to the intermediate input linkage, and thus shed some light on importance of considering sectoral linkage when discussing the carbon leakage issue of climate policies.
Keywords: Q55; Q58; Q43; Q48; O13; O31; O33; O44; F18; 330; Carbon Leakage; Sectoral Linkage; Climate Regulation; General Equilibrium Model; Production Substitution Effect; Multiplier Effect